Japanese Learner’s Ability to Pronounce Nasal Consonant /N/ Located at The End of Words - Sesefanakh, Alja Genedili; Febriyanti, Rike (Universitas Pendidikan Indonesia (Indonesia University of Education), 2022)
Japanese is a language that has a unique sound and distinctive articulation, but this uniqueness sometimes makes the pronunciation of people who are learning Japanese is still a lot less precise. Therefore, this study was conducted to find out the ability of Indonesian Japanese learners to pronounce the nasal consonant sounds located at the end of a word or called uvular nasal sounds, which is in Japanese 「口蓋垂鼻音」kougaisuibion with phonetic letter symbol /N/. This study was conducted on 12 Japanese language learners at SMAN 2 Batu, using a descriptive qualitative method and then using Praat to analyse their voices while reading 3 Japanese sentences consisting of the words [hitomisan], [sumimasen], and [imasen]. This study also analysed the voice of Japanese native speakers when reading the same sentences as Japanese learners use as a reference. The results of this study are pronunciation by native speakers found nasal sounds that are pronounced in the form of nasal uvular sounds /N/, also found the existence of pronunciation that cannot be distinguished between vowels and nasal consonants from the results of Praat analysis. While for students, there are only a few that have been appropriate such as native speakers’ pronunciation but most of them had different pronunciations.